写生, 写生 = Live and alive - Ng, Woon Lam (Ng Woon Lam, 2020)
En plein air painting is translated slightly differently in the Chinese language. It is not ‘outdoor painting’ but ‘writing from life’. As I am not a theorist but a practitioner, I will not focus on the theory of calligraphic behavior in painting. The name I used here “Live and Alive”, is to depict the life force of en plein air painting process. ‘Live’ describes the passive observation but it sublimes itself into an active visual participation, making the subject matters ‘Alive’. As a painter, one moment I could be inspired to work while another moment, I could be just using painting as an excuse for expression. To me, the essence of en plein air process surpasses mere observation of the subject matters. It should reach a higher level where viewers are able to emotionally perceive a painter’s creative signal. Brushwork constitutes a major part of my painting. It requires an ability to summarize subject matters into their most essential forms. With that requirement, the difficulty of the painting process multiplies. The observation process and selective visual behavior will decide the success of a painting journey. To partially ease the problem, I work heavily in sketches and drawing study before moving into actual painting. To be ambitious of my results, I chose to work with large format pieces though it is against the common en plein air practice. I hope to present to my audience a new meaning of en plein air paintings. The dynamics of time and space involved in en plein air painting process increases the level of difficulty for painters but allows surprises. I wish my artworks and presentation of exhibition could bring my audience a new visual experience. I hope to bridge their visual behavior with the other four senses, and thereby enhance their emotional response to paintings.